Numerical simulation of icing effects on static flow field around blade airfoil for vertical axis wind turbine - Yan, Li; Yuan, Chi; Yongjun, Han; Shengmao, Li; Kotaro, Tagawa (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: Icing on blade surface of the straight-bladed vertical axis wind turbine (SB-VAWT) set in cold regions is a serious problem. To study the performance effects of icing on SB-VAWT, numerical simulations were carried out on the ice accretion on NACA 0015 airfoil which was always used for blade airfoil of SB-VAWT by CFD methods based on 2D steady incompressible N-S Equation. The morphology and procedure of icing on blade airfoil were obtained under different wind speeds, attack angles of blade and water flow flux in wind. The static flow fields, especially the static pressure fields around blade airfoil with or without icing on it were computed. The aerodynamic characteristics including the lift and drag force coefficients of blade airfoil were also calculated. The results indicated that icing caused the static pressure field changed greatly and led to the increasing of drag force and reducing the aerodynamic performance. Keywords: vertical axis wind turbine (VAWT), icing, blade airfoil, static flow field, numerical simulation DOI: 10.3965/j.issn.1934-6344.2011.03.041-047 Citation: Li Yan, Chi Yuan, Han Yongjun, Li Shengmao, Tagawa Kotaro. Numerical simulation of icing effects on static flow field around blade airfoil for vertical axis wind turbine. Int J Agric & Biol Eng, 2011; 4(3): 41